Pattern of fixation explains atypical eye processing during observation of faces with direct or averted gaze in autism (results of the INFoR Cohort) - Olena V. Bogdanova; Volodymyr B. Bogdanov; Etienne Guillaud; Charles Laidi; Josselin Houenou; Richard Delorme; Myriam Ly‑Le Moal; Marion Leboyer; Manuel Bouvard; Jean‑René Cazalets; Anouck Amestoy (PLoS ONE, 2025)
One of the most reliable early predictors of autism is atypical social attention, particularly attenuated eye gaze contact. As a part of the InFoR cohort, a multicentric French longitudinal study, 88 autistic participants and 56 participants without autism performed a gaze discrimination task using 28 static pictures of faces with either direct or averted gaze. We monitored eye fixation behavior during face picture observation and analyzed subsequent key-press responses. The eyes of faces with direct gaze attracted more fixations than those of faces with averted gaze. Autistic participants showed significantly reduced Eye Fixations Indexes (EFI; a parameter derived from the number of fixations on eyes of the image; it reflects participant’s strategy of face observation) and longer response times (RTs), strongly and negatively correlated with each other. A mediational analysis demonstrated that the influence of group on RTs was mainly driven by the EFI. The EFI was related to the number of anticipatory saccades obtained for basic oculomotor tasks. The RTs were related to scores of Attention Deficit Hyperactivity Disorder Rating Scale (ADHD-RS), Behavior Rating Inventory of Executive Function (BRIEF) and severity of autism as tested by the Social Responsiveness Scale (SRS-2), but not to the level of social anxiety. Altogether we demonstrate that the eye fixation index during face observation was associated with attentional control and influenced judgment response of participants, while the task performance is affected by a wider range of individual variables.